The Effect of Betel Nut Extract (Areca catethu L) on Spermatozoa Quality (Macroscopic and Microscopic) in Male Goats - Yuni Oktaviani; Gianty Hartani Lugiana; Sadjatun Nisa; Kamelia Ningrum; Dwi Wijayanti (Buletin Peternakan, 2022)
The purpose of this study is to determine the effect of betel nut extract on the macroscopically and microscopically quality of spermatozoa. Materials and methods were used for 16 male Ettawa goats at the age of 2 years. The preparation of betel nut extract and macroscopic observations of spermatozoa via the use of odors, colors, and volumes, as well as microscopic observations of spermatozoa through the use of mass motion, mass motility, and individual motility. The betel nut extract was administered orally for 15 days. The treatments in this study were T0 (without the provision of betel nut extract), T1 (provision of betel nut extract (90 mg/goat/day)), T2 (provision of betel nut extract (180 mg/goat/day)), T3 (provision of betel nut extract (270 mg/goat/day)). The results showed that the addition of betel nut extract was significantly different than without extracts (P<0.05). The goats without betel nut extract had the lowest quality of spermatozoa, whereas the goats treated with a betel nut extract (270 mg/goat/day) had the highest quality of spermatozoa of all the treatments. There was an increase in spermatozoa in the 10th data collection, including smell, colour, volume, mass motility, and individual motility. Furthermore, male goats were given betel nut extract at a dose of 270 mg/goat/day, which improved spermatozoa quality both macroscopically and microscopically. Subsequently, we assumed that betel nut extract could improve reproductive quality in male goats.